Capital Investment, Asset Growth, Liqudity, And State Ownership On The Financial Performance Of State-Owned Enterprises - Tengku Muhamad Hasan As’ari; Rizal Yaya (Jurnal Reviu Akuntansi dan Keuangan, 2020)
Poor financial performance in some State-Owned Enterprises (SOEs) in the last decade have been at public’s concern. This study aims at analyzing the influence of capital contribution, asset growth, liqudity, and state ownership on financial performance of state-owned enterprises. The subject in this study is SOEs listed in the Indonesian Stock Exchange during 2015-2018. Eigthy samples were collected and analysed by using multiple regression analysis. The results of the statistical test shows that state ownership measured by percentage of shares owned by the government has a negative and significant effect on financial performance state-owned. Meanwhile other variables such as capital contribution, asset growth and liqudity have no effect on financial performance of state-owned enterprises. This indicates that SOEs with high government shares tend to have more external intervention than those with less Government shares. For the SOEs with high government shares, there is a strong need to be managed with more professional to have better financial performance.